The aerosol particle drift in a standing wave field - CZYŻ, Henryka (Archives of Acoustics, 1987)
This study considers the equation of motion of an aerosol particle in a standing wave field under the influence of drift and resistance forces in the Stokes and Oseen approximation. It evaluates the possibility of simplifying the equation of motion, taking into account the drift related to the radiation pressure, periodic viscosity changes and the asymmetry of motion of particle vibrating in a standing wave field. It gives the general properties of the solutions of motion equations for considerable attenuation and formulates the applicability of approximation which consists in neglecting the inertia of a particle.